2-Phenyl-2,3-dihydrobenzo[d]thiazole: A Mild, Efficient, and Highly Active in situ Generated Chemoselective Reducing Agent for the One-Pot Synthesis of 5-Monoalkylbarbiturates in Water - Kalita, Subarna Jyoti; Deka, Dibakar Chandra (Synlett, 2018)
A metal- and catalyst-free reductive alkylation protocol for the one-pot synthesis of 5-monoalkylbarbiturates from barbituric acids and aldehydes using the in situ generated chemoselective reducing agent 2-phenyl-2,3-dihydrobenzo[d]thiazole from 2-aminothiophenol and benzaldehyde is described. The notable advantages of the protocol are operational simplicity, mild reaction conditions, high yield, short reaction time, and simple workup and purification process which make it highly attractive.
Keywords: 5-monoalkylbarbiturates; benzothiazoline; transfer hydrogenation; aqueous media; metal- and catalyst-free